Morphometry of Baudoin Occipital condylar index in Dry Ossified Human Occipital Bone - Kashem, Kanetarin; Ara, Shamim (Bangladesh Journal of Anatomy, 2020)
Context: The occipital condyles of the skull articulate with the superior articular facets of the atlas vertebra and form an important junction between the cranium and the vertebral column. The great vital important neuroanatomical structures such as spinal cord, vertebral arteries, nerves and meninges are passing through the foramen magnum. In case of fragmentary human remains where no other skeletal remains are preserved the intact occipital region may be useful for determining the sex of the individuals. So morphometric data of occipital condylar index is essential in anthropologist and neurosurgeons for various surgical diagnosis and treatment. Baudoin condylar index is a sex determination method based on measurements of length and width of the occipital condyle. This study was performed by the help of this Baudoin condylar index method. Materials and Methods: A cross sectional analytical type of study was conducted in the Department of Anatomy, Dhaka Medical College, Dhaka from January 2011 to December 2011. The length, width of occipital condyle and condylar index were measured with the help of digital slide calipers. Results: The mean ± SD occipital condylar index was significantly higher (p<0.001) in male than in female. Bangladesh Journal of Anatomy July 2020, Vol. 18, No. 2, pp. 28-31